2022
DOI: 10.3389/fnins.2022.1042824
|View full text |Cite
|
Sign up to set email alerts
|

New insights in addressing cerebral small vessel disease: Associated with extracellular fluid in white matter

Abstract: ObjectiveTo explore the role of extracellular fluid, assessed by diffusion tensor imaging (DTI) metrics of free water (FW), in the white matter of patients with cerebral small vessel disease (CSVD).Materials and methodsThe baseline clinical and imaging data of 129 patients with CSVD were collected and reviewed. CSVD MR markers, including periventricular white matter hyperintensity (PWMH), deep white matter hyperintensity (DWMH), cerebral microbleed (CMB), enlarged perivascular space (PVS), and lacunar infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In a further study of the same community cohort and additionally comparative CSVD cohort, Huang et al [ 66 ] showed that the positive association between ePVS and free water exists in both healthy participants and in CSVD patients. Lan et al [ 67 ] further supported this association in CSVD patients, demonstrating that a higher number of BG ePVS correlated with higher free water volumes.…”
Section: Resultsmentioning
confidence: 87%
“…In a further study of the same community cohort and additionally comparative CSVD cohort, Huang et al [ 66 ] showed that the positive association between ePVS and free water exists in both healthy participants and in CSVD patients. Lan et al [ 67 ] further supported this association in CSVD patients, demonstrating that a higher number of BG ePVS correlated with higher free water volumes.…”
Section: Resultsmentioning
confidence: 87%